CMR analysis of the cardioprotective effects of chronic statin therapy prior to first STEMI: a propensity score analysis. (14th October 2021) - Mendieta Badimon, G; Calvo, M; Guzman, J; Perez, P; Alamar, M; Vilahur, G; Gavara, J; Vargas, S; Rello, P; Valente, F; Rios, J; Badimon, L; et al.
Abstract: Background: In addition to their lipid-lowering properties, statins possess cardioprotective effects. However, the impact of the latter on acute cardioprotection and adverse left ventricular (LV) remodelling following ST-elevation myocardial infarction (STEMI) have not been investigated through cardiac magnetic resonance (CMR) analysis to date. Purpose: To investigate the cardioprotective effects of chronic oral statin treatment prior to first STEMI. Methods: The study included 1236 patients with a first STEMI and a CMR performed during the index admission. Among them, 923 underwent a second CMR at 6 months follow-up. The effects of chronic oral statin treatment prior to STEMI on acute infarct size (IS) as a percentage of LV mass, LV ejection fraction (LVEF), microvascular obstruction (MVO), and changes in LV end-diastolic volume (EDVi) and end-systolic volume indexes (ESVi)] at 6 months were evaluated. A propensity score to receive treatment prior to STEMI with statins was calculated based on the inverse probability of treatment weighting (IPTW) from the following parameters: age on admission, sex, smoking status, type 2 diabetes, hypertension, family history of coronary artery disease, current co-treatments (ACEis/ARBs and/or beta-blockers), heart rate (HR), blood pressure (BP) and creatinine levels on admission, and pre-PCI TIMI flow in the culprit artery. Results were stratified according to a symptom-to-balloon time (S2Bt) ≤ or >3 hours. Results: The study population's median age was 59 years (IQR 50–68), 16.3% were women; 18.9% were receiving treatment with statins prior to STEMI (table 1). Despite no effect on MVO occurrence (OR: 0.81 [0.60; 1.09], p=0.166), prior treatment with statins was associated with a reduction in IS (18.43% [16.67; 20.19] vs 21.50% [20.67; 22.34], p=0.002), particularly among subjects with ≤3 hours of S2Bt. Accordingly, prior treatment with statins conferred a benefit in mean baseline LVEF (50.23% [48.73; 51.73] vs 48.15% [47.43; 48.87], p=0.014). At 6 months, treatment with statins prior to STEMI blunted the changes in EDVi and ESVi, but only among patients with ≤3 hours of S2Bt (table 2). In addition, a reduction in the probability of adverse LV remodelling, defined as an increase in ESVi >10%, was observed in statin pre-treated patients (OR: 0.67 [0.45; 0.99], p=0.043). Conclusion: Treatment with statins before STEMI is associated with improved indexes of cardioprotection as assessed by CMR, particularly among subjects with S2Bt ≤3 hours. Those effects seem to have an impact in limiting adverse LV remodelling as early as 6 months follow-up, and a greater than 10% change in ESVi. These findings warrant further and prospective evaluation of the potential cardioprotective effects of chronic oral statin treatment prior to STEMI. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): This study was partially funded by several grants from Fundaciό La Marato TV3 (2015 30 31 32), Instituto de Salud Carlos III (FIS15/00531) and La Caixa Banking Foundation (HR17-00527).